Operational reproducing kernel Hilbert spaces - Senkienė, E.; Tempelman, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. Сенкене, А. Темпельман. Гильбертовы пространства с операторными воспроизводящими ядрамиE. Senkienė, A. Tempelmanas. Hilberto erdvės su operatoriniais reprodukuojančiais branduoliais